Around the Legal Concept of Revolution - Deprez, Guillaume (Teisė, 2024)
The question of the legal concept of revolution is a multidisciplinary one that certainly requires an interest in law, philosophy, history and political science. However, in order to maintain a purely legal vision of the concept, the intersection of these disciplines may seem counterproductive to some. There seem to be two opposing ways of thinking about revolution in the legal sense. For the advocates of legal positivism, the working methodology must be entirely legal. In this sense, they follow the teachings of Hans Kelsen, who proposes to study the legal revolution from a legal point of view (1). In reaction to this vision and in order to fill its blind spots, others have preferred a material approach, reversing the formal analysis developed by the father of normativism (2). Considering these two schools of thought, diametrically opposed in many respects, the question arises: is there a middle way? Undoubtedly, it is in this third option that we can read the work of Bruce Ackerman and others. This typology allows us to sketch the methodological possibilities of a legal interpretation of the concept of revolution, without, however, being able to offer a new and completely fresh interpretation that is independent of the presuppositions presented in this article.